Study of Measuring The Cover Factor of Woven Fabrics Using Image Processing Techniques - Wijayono, Andrian; Murti, Wilda (Universitas Insan Cendekia Mandiri, 2024)
In this research, a method for measuring the cover factor of woven fabric using digital image processing techniques has been developed. The cover factor of woven fabric is measured by capturing a digital image of the fabric under examination using a digital microscope, converting the image into digital image information, storing this digital image information in digital memory, and performing digital image segmentation to determine the cover factor of the woven fabric. Cover factor measurements were conducted on seven samples of woven fabric with different densities. To validate the proposed method, the cover factor measurements obtained from image processing were compared with the theoretical cover factor obtained from the standard method. It was found that there was no significant difference between the results obtained from the conventional method and the proposed method (with a significance value of 0.95).